Computational search of hybrid human/SARS-CoV-2 dsRNA reveals unique viral sequences that diverge from those of other coronavirus strains. Issue 6 (June 2021) - Pasquier, Claude; Robichon, Alain
Abstract: The role of the RNAi/Dicer/Ago system in degrading RNA viruses has been elusive in mammals in the past, which has prompted authors to think that interferon (IFN) synthesis is essential in this clade, relegating the RNAi defense strategy against viral infection as an accessory function. However, recent publications highlight the existence of abundant viral small interference and micro RNAs (VsiRNAs and VmiRNAs) in both cell-line and whole organism based experiments, indicating a contribution of these molecules in host responses and/or viral replication. We explore the theoretical possibility that RNAi triggered by SARS-CoV-2 might degrade some host transcripts in the opposite direction, although this hypothesis seems counterintuitive. The SARS-CoV-2 genome was therefore computationally searched for exact intrapairing within the viral RNA and exact hybrid pairing with the human transcriptome over a minimum of 20 bases in length. Minimal segments of 20-base lengths of SARS-CoV-2 RNA were found based on the theoretical matching with existing complementary strands in the human host transcriptome. Few human genes potentially annealing with SARS-CoV-2 RNA, including mitochondrial deubiquitinase USP30, the subunit of ubiquitin protein ligase complex FBXO21 and two long noncoding RNAs, were retrieved. The hypothesis that viral-originated RNAi might mediate degradation of host transcriptome messages was corroborated by published high throughput sequencing of RNA from infected tissues and cultured cells, clinical observation and phylogenetic comparative analysis, indicating a strong specificity of these SARS-CoV-2 hybrid pairing sequences for human genomes. Abstract : SARS-CoV-2; dsRNA; Dicer; RNA cleavage; Host transcriptome; Viral genome.